The Effect of Financial Literacy and Financial Behavior on Religiusity Moderated by Investment Decisions - Imam Syafiq Mughni Al Hakim; Muhammad Jihadi; Warsono (Universitas Muhammadiyah Malang, 2023)
This study aims to determine the effect of financial literacy and financial behavior on investment decision variables through religiosity as a moderating variable. The number of samples in this study was 150 respondents with a purposive sampling method. The object of this research is students of three universities in Malang city. The data analysis method used is Moderated Regression Analysis (MRA) with SPSS 26 software. The results of this study indicate that financial literacy has a significant effect on investment decisions, financial behavior has a significant effect on investment decisions, financial literacy and financial behavior simultaneously significantly influence investment decisions. In addition, religiosity strengthens the relationship of financial literacy to investment decisions. Â